THE UTILISATION OF FINANCIAL TECHNOLOGY (FINTECH) LENDING SERVICES IN ACEH SOCIETY PRACTICES: Effectiveness Analysis of the Implementation of Qanun LKS - Deka Oki Saputra (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2024)
The utilisation of online financial technology (fintech) lending services by the people of Aceh is quite large. The Aceh Provincial Financial Services Authority (OJK) noted an increase in the practice of Acehnese people interacting with fintech lending companies that have doubts about their sharia. Currently, the Qanun on Sharia Financial Institutions (LKS) only regulates direct lending between Acehnese and Aceh-based LKS companies. Therefore, this paper aims to analyse the effectiveness of the implementation of the Qanun LKS in the practice of Acehnese people using fintech lending services. This research is studied with two approaches, namely conceptual approach and statute approach, with the type of normative legal research. The nature of this research analysis is prescriptive. The results showed that the development of fintech lending technology provides opportunities, making it easier for the people of Aceh to obtain online loans using only a website or smartphone application. There is an increase in online loan interactions with fintech lending companies made by the people of Aceh from year to year. In the context of legal regulation in Aceh, Qanun LKS only regulates direct loan financing through LKS companies operating in Aceh. Thus, in terms of legal effectiveness, the application of Qanun LKS to the utilisation of fintech lending services in Acehnese practice has not been effective. There are 4 indicators, namely there is no legal material for Qanun LKS that regulates sharia-based fintech lending, there is no law enforcer who oversees fintech lending traffic in Aceh, there are no facilities and infrastructure for law enforcement in fintech lending, and the lack of legal culture and legal awareness of the people of Aceh.